2008
DOI: 10.1111/j.1467-937x.2008.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Lenders and Corporate Distress: Evidence on Debt Restructuring

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(82 citation statements)
references
References 26 publications
(31 reference statements)
8
69
0
5
Order By: Relevance
“…The experimental results of this paper are consistent with the findings from recent empirical studies. Brunner and Krahnen [] document that moderate‐sized “bank pools” have a positive impact on the success of a distressed loan workout in Germany. Bank pools are cheap talk in that they are formed to allow multiple creditors to communicate with each other through nonbinding guarantees.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results of this paper are consistent with the findings from recent empirical studies. Brunner and Krahnen [] document that moderate‐sized “bank pools” have a positive impact on the success of a distressed loan workout in Germany. Bank pools are cheap talk in that they are formed to allow multiple creditors to communicate with each other through nonbinding guarantees.…”
Section: Resultsmentioning
confidence: 99%
“…3 Empirical studies in the USA, Germany and Italy indicate that relationship lending increases credit availability for private firms (Berger & Udell, 1995;Bharat, Dahiya, & Saunders, 2011;Bolton et al, 2013;Harhoff & Körting, 1998). Relationship lenders are also more likely than other lenders to provide liquidity support in the event of financial distress (Brunner & Krahnen, 2008;Couwenberg & de Jong, 2006;Puri et al, 2013).…”
Section: Relationship Lending and Financial Reporting Qualitymentioning
confidence: 95%
“…The relationship lending literature argues that a close relationship enables the bank to acquire private information about the firm's credit risk over time and to influence the firm's management, reducing information asymmetries and agency problems (Berger & Udell, 1995;Boot, 2000;Elsas, 2005;Rajan, 1992). Consequently, there is evidence that private firms with strong bank relationships are less credit-constrained (Berger & Udell, 1998;Bolton, Freixas, Gambacorta, & Mistrulli, 2013;Petersen & Rajan, 1994) and that relationship lenders are more likely than other lenders to provide liquidity support in the event of financial distress (Brunner & Krahnen, 2008;Couwenberg & de Jong, 2006;Puri, Rocholl, & Steffen, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Multiple bank relationships make it difficult for creditors to coordinate with each other, particularly in the case of business restructuring, and thus increase the risk for customer firms (Dewatripont and Maskin 1995;Bolton and Scharfstein 1996;Foglia et al 1998;Brunner and Krahnen 2008). In contrast, some studies have shown that multiple bank relationships reduce the theoretical firm bankruptcy risk.…”
Section: Introductionmentioning
confidence: 93%